Eimeria maxima microneme protein 2 delivered as DNA vaccine and recombinant protein induces immunity against experimental homogenous challenge. Issue 5 (October 2015) - Huang, Jingwei; Zhang, Zhenchao; Li, Menghui; Song, Xiaokai; Yan, Ruofeng; Xu, Lixin; Li, Xiangrui
Abstract E. maxima is one of the seven species of Eimeria that infects chicken. Until now, only a few antigenic genes of E. maxima have been reported. In the present study, the immune protective effects against E. maxima challenge of recombinant protein and DNA vaccine encoding EmMIC2 were evaluated. Two-week-old chickens were randomly divided into five groups. The experimental group of chickens was immunized with 100 μg DNA vaccine pVAX1-MIC2 or 200 μg rEmMIC2 protein while the control group of chickens was injected with pVAX1 plasmid or sterile PBS. The results showed that the anti-EmMIC2 antibody titers of both rEmMIC2 protein and pVAX1-MIC2 groups were significantly higher as compared to PBS and pVAX1 control (P < 0.05). The splenocytes from both vaccinated groups of chickens displayed significantly greater proliferation compared with the controls (P < 0.05). Serum from chickens immunized with pVAX1-MIC2 and rEmMIC2 protein displayed significantly high levels of IL-2, IFN-γ, IL-10, IL-17, TGF-β and IL-4 (P < 0.05) compared to those of negative controls. The challenge experiment results showed that both the recombinant protein and the DNA vaccine could obviously alleviate jejunum lesions, body weight loss, increase oocyst, decrease ratio and provide ACIs of more than 165. All the above results suggested that immunization with EmMIC2 was effective in imparting partial protection against E. maxima challenge and it could be an effective antigen candidate for the development of new vaccines against E. maxima.